Distribution of Human Papillomavirus Genotypes among HIV-Positive and HIV-Negative Women in Cape Town, South Africa - McDonald, Alicia C.; Tergas, Ana I.; Kuhn, Louise; Denny, Lynette; Wright, Thomas C. (Frontiers in Oncology, 2014)
Objective: HIV-positive women are known to be at high risk of Human Papillomavirus (HPV) infection and its associated cervical pathology. Here we describe the prevalence and distribution of HPV genotypes among HIV-positive and negative women in South Africa, with and without cervical intraepithelial neoplasia (CIN). Methods: We report data on 1,371 HIV-positive women and 8,050 HIV-negative women, aged 17-65 years, recruited into three sequential studies in Cape Town, South Africa, conducted among women who had no history of cervical cancer screening recruited from the general population. All women were tested for HIV. Cervical samples were tested for high risk HPV DNA (Hybrid Capture 2) with positive samples tested to determine the specific genotype (Line Blot). CIN status was determined based on colposcopy and biopsy. Results: The HPV prevalence was higher among HIV-positive women (52.4%) than among HIV-negative women (20.8%) overall and in all age groups. Younger women, aged 17-19 years, had the highest HPV prevalence regardless of HIV status. HIV-positive women were more likely to have CIN 2 or 3 than HIV-negative women. HPV 16, 35, and 58 were the most common high-risk HPV types with no major differences in the type distribution by HIV status. HPV 18 was more common in older HIV-positive women (40-65 years) with no or low grade disease, but less common in younger women (17-29 years) with CIN 2 or 3, compared to HIV-negative counterparts (p< 0.03). Infections with multiple high-risk HPV types were more common in HIV-positive than HIV-negative women controlling for age and cervical disease status. Conclusion: HIV-positive women were more likely to have high risk HPV than HIV-negative women but among those with HPV, the distribution of HPV types was similar by HIV status. Screening strategies incorporating HPV genotyping and vaccination should be effective in preventing cervical cancer in both HIV-positive and negative women living in sub-Saharan Africa.